Microorganisms isolated from external ear cultures and their antimicrobial susceptibility in patients with chronic suppurative otitis media: A six years experience (Annals of Medical Research, 2021)
Aim: Chronic suppurative otitis media (CSOM) continues to be a major health issue in developing countries. The goal of this study was to establish the microorganisms causing CSOM and their susceptibility to antimicrobials.Materials and Methods: External ear tract swab that came to our laboratory between 2014-2019 were evaluated retrospectively. The data were obtained from the hospital medical records. Data was collected using an electronic database. Results: The analysis included 185 ear swab samples. These patients 55.1% male and 44.9% female, and average age was 44.29 ± 1.6 (2-86) years. Forty (21.6%) of the patients included in the study were diagnosed with cholesteatoma as having chronic suppurative otitis media. The first three bacteria species isolated from the samples included in the study; Pseudomonas aeruginosa (31.9%), Staphylococcus aureus (11.9%) and Escherichia coli (9.7%). In addition, in 10.8% of the samples Candida spp. and in 5.4% of the samples Aspergillus spp. were isolated. The first three species isolated from the patients with cholesteatoma; P. aeruginosa (6.5%),S. aureus (4.3%) and Candida spp. (3.2%), the first three species isolated in patients without cholesteatoma; P. aeruginosa (25.4%), E. coli (8.1%), S. aureus and Candida spp. (7.6%) was detected. Ciprofloxacin (68.8%) and gentamicin (46.7%) in P. aureginosa isolates, amoxicillin-clavulonic acid (66.7%) and trimethoprim-sulfamethoxazole (42.9%) in E. coli isolates were found to be the most resistant antimicrobials.Conclusion: In conclusion, antimicrobial therapy should not be initiated in CSOM patients without waiting for the culture result. However, in cases where empirical antimicrobial therapy is mandatory, the first choice has been determined as amikacin. Good awareness of microorganisms’ antimicrobial sensitivity can lead to appropriate antibiotic usage and treatment success for CSOM. We think that multicenter prospective studies are needed to organize effective treatments of these infections.
Keywords: Antimicrobial susceptibility; chronic suppurative otitis media; microorganisms